Some Characteristics of Communication Verb Ask in Newspaper Discourse - Tomić, Božana; Jelena Š.Novaković, PhD (European Journal of Multidisciplinary Studies, 2017)
This paper deals with communication verb ask in newspaper discourse. Analysing examples from our corpus we wanted to show lingustic characteristic of the verb ask in this type of written discourse. The analysis shows that the verb is used in more or less similar structures as elsewhere. However, the colligation patterns it occurrs in are something of a novelty and typical of this type of discourse.
Keywords: Some Characteristics of Communication Verb Ask in Newspaper Discourse